Selective Approach in Managing Penetrating Neck Injury - Ahmed, Raid Jasim; Hammoud, Haitham Abid; Majeed, Ghassan Hikmat (AL-Kindy College Medical Journal, 2016)
Background: Penetrating Neck Injuries (PNI) management represents a challenge to most surgeons in civilian trauma, in weighing selective versus mandatory exploration of all cases in different circumstances. Data are encouraging surgeons to adopt the former approach.Objectives: The study aims to assess the selective approach in our war and terror time events in Al-Yarmouk teaching hospital.Type of the study:A retrospective study. Methods: Data of patients presented to the Thoracic and Vascular ward in Al-Yarmouk teaching hospital with PNI were assessed retrospectively, from March 2013 to March 2015, and analyzed for epidemiology, mechanism of trauma, management methods, associated organ injuries, complications and mortality. Results: Among 83 patients (76 males and 7 females) who presented with PNI, the mean age was 28.5±15 years with a peak incidence in third decade. Shell injury (52.2%) was the most common mechanism and zone II was the most frequently injured (49.4%). Therapeutic exploration of neck in 82% of the cases, a decision of surgical exploration (87%) patients. Vascular injuries were the most identified neck structures (39.5%). Chest injuries (35%) were the most common associated injuries identified in patients who had additional anatomic region injury (41%) beside PNI. Complication rate of 18% and infection (26.6%) were most common and mortality rate was 8%. Conclusions: Still the selective approach is preferable in management of PNI in our war and terror time circumstances and limited resources of country.